2012
DOI: 10.1038/nn.3136
|View full text |Cite
|
Sign up to set email alerts
|

The neuroscience of race

Abstract: As the racial composition of the population changes, intergroup interactions are increasingly common. To understand how we perceive and categorize race and the attitudes that flow from it, scientists have used brain imaging techniques to examine how social categories of race and ethnicity are processed, evaluated and incorporated in decision-making. We review these findings, focusing on black and white race categories. A network of interacting brain regions is important in the unintentional, implicit expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
167
4
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(182 citation statements)
references
References 94 publications
(109 reference statements)
8
167
4
3
Order By: Relevance
“…Previous research suggested that this region plays an important role in emotion reappraisal and regulation (Golkar et al 2012). This is further supported by findings that show dlPFC engagement in a regulatory mechanism that controlled implicit and potentially unwanted racial associations and racially biased responses in previous cross cultural studies (Ito and Bartholow 2009;Kubota et al 2012). In order to investigate the neural correlates of automatic and controlled social evaluation, Cunningham et al (2004) presented European-American participants who reported a strong motivation to control prejudice with either subliminal (30 ms) or 525 ms presentations of pictures of European-American and African-American faces.…”
Section: Effect Of Culture On Anger Expressed With Direct Gazementioning
confidence: 59%
“…Previous research suggested that this region plays an important role in emotion reappraisal and regulation (Golkar et al 2012). This is further supported by findings that show dlPFC engagement in a regulatory mechanism that controlled implicit and potentially unwanted racial associations and racially biased responses in previous cross cultural studies (Ito and Bartholow 2009;Kubota et al 2012). In order to investigate the neural correlates of automatic and controlled social evaluation, Cunningham et al (2004) presented European-American participants who reported a strong motivation to control prejudice with either subliminal (30 ms) or 525 ms presentations of pictures of European-American and African-American faces.…”
Section: Effect Of Culture On Anger Expressed With Direct Gazementioning
confidence: 59%
“…At least three different strategies can be implemented in these cases (for review on the strategies listed see Kubota et al, 2012):…”
Section: Implementation Of Egalitarian Goals: Enhancing Self-regulatimentioning
confidence: 99%
“…This interdisciplinary approach-termed social neuroscience ( To date, intergroup and cultural neuroscience has largely focused on specific social groups rather than studying the dynamics that govern group formation and intergroup interactions. Several excellent reviews have examined the neural basis of social categorization along boundaries marked by visual cues to targets' group membership, such as race, sex, and age (e.g., Eberhardt, 2005;Ito & Bartholow, 2009;Kubota et al, 2012); however, broader inferences The neuroscience of intergroup relations 5 about group processes are often difficult to make on the basis of these social categories due to confounding variables (e.g., differences in the visual appearance of target stimuli, associated stereotypes and prejudices, and perceivers' personal experience with groups in question).…”
Section: The Neuroscience Of Intergroup Relationsmentioning
confidence: 99%
“…This interdisciplinary approach-termed social neuroscience ( To date, intergroup and cultural neuroscience has largely focused on specific social groups rather than studying the dynamics that govern group formation and intergroup interactions. Several excellent reviews have examined the neural basis of social categorization along boundaries marked by visual cues to targets' group membership, such as race, sex, and age (e.g., Eberhardt, 2005;Ito & Bartholow, 2009;Kubota et al, 2012); however, broader inferences The neuroscience of intergroup relations 5 about group processes are often difficult to make on the basis of these social categories due to confounding variables (e.g., differences in the visual appearance of target stimuli, associated stereotypes and prejudices, and perceivers' personal experience with groups in question).Furthermore, research that focuses exclusively on a single, static category boundary fails to account fully for the flexible nature of social identity representation (e.g., the effects of context on self-categorization, the effects of task on person construal; Freeman & Ambady, 2011). Thus, the next phase of intergroup neuroscience research must account for the fact that not all outgroups are equivalent, not all group memberships are static, and which group identities are salient is highly context dependent (Turner, Oakes, Haslam, & McGarty, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation